Economics of Mixed Plantation of Prosopis juliflora and Acacia nilotica for Fuel in Agra Ravines - Babu, Ram; Puri, D N; Singh, J P; Sharma, S K (Annals of Arid Zone, 2016)
Economic analysis of the mixed plantalion of Acacla nilotica (60%) Prosopis juliflora (20% and miscellaneous species (20%) in severe ravine lands along (he bank of river Yamuna at Agra, was earned out. The benefit-cost ratios of the first 15 years rotation at 10% an:! 15% discount rates .,.,ere worked out to be 1.81 and 1.09, respectively wilh internal rate of return (IRR) of 16.2%. Twenty percent of the area covered with Prosopis juliflora in the first rotation coppiced profusely and was retained. The remaining area was resown with Prosopis juliflora. The benefit-cost ratios of the second rotation of seven years (Prosopis juliflora- 78% and miscellaneous species-22%1 worked out to be 1.61 and 1.40 at 10% and 15% discount rates having IRR of 27%. Both the rotations gave a favourable benefit-cost ratio which establishes the economic feasibility of raising mixed plantation of Prosopis juliflora and Acacla nilotica in ravine lands whose opportunity cost is very low.